The use of drama activities to develop speaking skills in students from conversational English groups of Colegio Técnico Profesional Cóbano = El uso de actividades de drama para desarrollar habilidades orales en estudiantes de grupos conversacionales de inglés del Colegio Técnico Profesional Cóbano - Montero Alfaro, Berny 1997- (2023)
This study reports on the effectiveness of using drama activities to improve speaking ability in seventh grade students from conversational classes. This research study developed a mixed methodology and a Quasi- Experimental method, which made it possible to compare two groups of students: an experimental one and a control one. The participants were 12 students from the experimental group and 12 students from the control group, both in a seventh grade group of the Cóbano Professional Technical College of the Peninsular Regional Office during the first and second school term 2022. The main objective of this research was to evaluate the possible effectiveness of the constant use of drama activities to examine oral skills with a sample population by carrying out tests before and after the activities developed in class. It was found that the experimental group improved their fluency by 75% (6 students) in terms of spontaneity compared to the control group, which had a setback in the results obtained in both tests. The results revealed that the use of theater activities is effective in improving the oral proficiency of the students. Also, it was possible to obtain qualitative results that reflect great benefits to the final results such as motivation, creativity and confidence. Finally, the researchers concluded that through the implementation of drama activities in conversational English classes, students can improve their mastery of speaking skills since the activities promote positive experiences in them. Finally, it is similarly recommended that researchers who wish to replicate studies be able to have longer periods of time in terms of the application of drama activities to obtain better results.